'I still have difficulties feeling like a mother': The transition to motherhood of preterm infants mothers. Issue 2 (1st February 2016) - Spinelli, Maria; Frigerio, Alessandra; Montali, Lorenzo; Fasolo, Mirco; Spada, Maria Simonetta; Mangili, Giovanna
Abstract : Objective: The premature birth of their infant can constitute a sudden interruption of the transition to motherhood that requires a reorganisation of the process. The present study aimed to analyse the experience of the transition to motherhood of preterm infants' mothers, framing it within Stern's transition to motherhood theory. Method: A semi-structured interview was administered to 30 mothers during the recovery of the infant in the Neonatal Intensive Care Unit. The interview explored the experience of mothers related to pregnancy, the infant's birth and recovery. Results: Thematic Analyses evidenced four interrelated themes: disconnection from the child, perception of maternal inadequacy, loss of parental role and temporal suspension. The themes showed that the mothers' experience of preterm birth not only concerns the traumatic delivery, but is also embedded in the entire process of becoming a mother within an institutional context. Conclusions: Results were connected to Stern's theory. Findings revealed difficulties for preterm mothers that could affect the development of the maternal constellation and thus their transition to motherhood. These difficulties may influence the construction of maternal identity, mother's representation of their child and the bond with their child.